The Transnational Mosque - Tammy Gaber (International Institute of Islamic Thought, 2016)
This catchy title, The Transnational Mosque, is timely and implies an analysis of global Islam and the multiplicities of mosque construction today. The premise promises to contribute to the scholarship on Islamic architecture, and yet there are some issues with the argument’s structure and even greater ones with the analytical depth with respect to architecture.